A genome-wide landscape of mRNAs, lncRNAs, and circRNAs during subcutaneous adipogenesis in pigs - Xin Liu; Kaiqing Liu; Baosen Shan; Shengjuan Wei; Dongfeng Li; Haiyin Han; Wei Wei; Jie Chen; Honglin Liu; Lifan Zhang (Journal of Animal Science and Biotechnology, 2018)
Abstract Background Preadipocyte differentiation plays a critical role in subcutaneous fat deposition in pigs. However, the roles of different RNAs, such as messenger RNAs (mRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) in the differentiation process of subcutaneous preadipocytes, are still largely unclear. In the present study, a transcriptome analysis, including the analysis of mRNAs, lncRNAs, and circRNAs, during different differentiation stages, namely, day 0 (D0), day 2 (D2), day 4 (D4), and day 8 (D8), of subcutaneous preadipocytes from Chinese Erhualian pigs was performed. Results A total of 1554, 470, 1344, 1777, and 676 differentially expressed (DE) mRNAs, 112, 58, 95, 136, and 93 DE lncRNAs, and 902, 787, 710, 932, and 850 DE circRNAs were identified between D2 and D0, between D4 and D2, between D8 and D4, between D4 and D0, and between D8 and D0, respectively. Furthermore, functional enrichment analysis showed that the common DE mRNAs during the entire differentiation process were mainly involved in lipid metabolic and cell differentiation processes. Additionally, co-expression network analysis identified the potential lncRNAs related to adipogenesis, e.g., MSTRG.131380 and MSTRG.62128. Conclusions Our study provides new insights of the expression changes of RNAs during adipogenic differentiation, which might contribute to the phenotype of subcutaneous adipogenesis. These results greatly improve our understanding of the molecular mechanisms regulating subcutaneous fat deposition in pigs.